2021
DOI: 10.3389/fvets.2021.725386
|View full text |Cite
|
Sign up to set email alerts
|

Neural Derivates of Canine Induced Pluripotent Stem Cells-Like Cells From a Mild Cognitive Impairment Dog

Abstract: Domestic dogs are superior models for translational medicine due to greater anatomical and physiological similarities with humans than rodents, including hereditary diseases with human equivalents. Particularly with respect to neurodegenerative medicine, dogs can serve as a natural, more relevant model of human disease compared to transgenic rodents. Herein we report attempts to develop a canine-derived in vitro model for neurodegenerative diseases through the generation of induced pluripotent stem cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…While colonies could be obtained with this method it was only when highly defined media was used, and still the reprogramming efficiency was very low ( 94 ). Chandrasekaran et al also used episomal reprogramming with electroporation, but even though morphological changes were observed in the cells, complete reprograming was not achieved and lentivirus was used subsequently, resulting in generation of canine iPSCs from the same somatic cells ( 95 ).…”
Section: “Step-by-step” Approach For Generating Ipscs In Companion An...mentioning
confidence: 99%
See 2 more Smart Citations
“…While colonies could be obtained with this method it was only when highly defined media was used, and still the reprogramming efficiency was very low ( 94 ). Chandrasekaran et al also used episomal reprogramming with electroporation, but even though morphological changes were observed in the cells, complete reprograming was not achieved and lentivirus was used subsequently, resulting in generation of canine iPSCs from the same somatic cells ( 95 ).…”
Section: “Step-by-step” Approach For Generating Ipscs In Companion An...mentioning
confidence: 99%
“…When it comes to the applicability of iPSCs in companion animals, reports are scarcer than for their generation and mainly focus on therapeutics or disease modeling. Therapeutic use of iPSCs has been mainly proposed for musculoskeletal conditions in horses ( 60 63 , 88 , 127 129 ) and for neurological and cardiovascular conditions in dogs ( 67 , 95 , 130 133 ). In terms of disease modeling, equine iPSCs can also be used for neurological conditions ( 58 , 134 ).…”
Section: Applications Of Ipscs In Companion Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this canine model demonstrated successful delivery, undifferentiated ciPSCs are not directly amenable for clinical transplantation due to higher risk of teratoma formation [ 22 ]. ciPSCs can be differentiated into either progenitor cells or adult cells such as neural, cardiac, endothelial, and platelets [ 16 , 22 , 38 , 93–96 ]. A summary of research studying the clinical applications of ciPSCs to date is shown in Table 3 .…”
Section: Potential Clinical Utility Of Cipscsmentioning
confidence: 99%
“…A similar study to Chow et al (2020) by Chandrasekaran et al (2021) differentiated ciPSC-like cells into NPCs that were used to repair damaged nervous tissue in dogs [ 93 ]. They found that despite incomplete reprogramming of ciPSCs, canine NPCs had reduced axonal fasciculation and shorter neuritis, demonstrating lower mature neuronal differentiation efficiency than human NPCs [ 93 ].…”
Section: Potential Clinical Utility Of Cipscsmentioning
confidence: 99%